A Note on Furstenburg Families and Shadowing in Topological Spaces. Issue 1 (2nd January 2019) - Ahmadi, Seyyed Alireza
ABSTRACT: In this note we use the concepts of lower density and upper density for elements of Furstenburg families to measure the set of error times in the shadowing process in non-metrizable topological spaces. We show that the measure of errors is the same for all iterations of a dynamical system.